Respon dan Produktivitas Padi Rawa terhadap Cekaman Rendaman Stagnan untuk Pengembangan di Lahan Rawa Lebak - ,, Yullianida; Ardie, Sintho Wahyuning; ,, Suwarno; Aswidinnoor, Hajrial (Indonesia Society of Agronomy (PERAGI) and Department of Agronomy and Horticulture, Faculty of Agriculture, IPB University, Bogor, Indonesia, 2015)
ABSTRACTThe limited fertile land and increasing flood intensity as a result of global climate changes become serious constraints in the sustainability of national rice production. Improvement of rice varieties, especially for rice cultivation in swampy area is necessary. The objective of this research were to evaluate responses and productivity of rice genotypes to stagnant flooding stress which occurs on swampy area. A total of 22 genotypes had been tested, included Tapus, IR42, and IR64 as check varieties. Water level at stagnant flooding environment was 50-60 cm and started from 35 days after planting until harvest. Research was conducted in wet season of 2011/2012 at Babakan Experimental Farm, Bogor Agricultural University. The experiment used randomized block design with three replicates. The results showed that stagnant flooding stress caused an increase in plant height, flowering and maturity date, number of unfilled grain, and stem elongation ability. On the other hand, the number of productive tiller and the number of filled grain decreased. The number of filled grain positively correlated with grain yield (r = 0.74**), but stem elongation ability didn’t have strong correlation with grain yield (r = -0.29). Genotypes IPB107-F-5-1-1 and IPB107-F-82-2-1 showed the highest productivity, 5.47 ton ha-1 and 5.80 ton ha-1,, respectively, at which productivity decreased up to 20% compared to optimum condition. Keywords: basin swampy rice, stagnant flooding